PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXPLICIT INSTRUCTION DALAM MENINGKATKAN HASIL BELAJAR IPS PADA SISWA KELAS IX SMP NEGERI 2 BONTORAMBA KABUPATEN JENEPONTO TAHUN PELAJARAN 2017/2018 - Ridawati Ridawati; Suwardi Annas; Saripuddin D; Muh Yahya (Jurnal Ilmiah Pena: Sains dan Ilmu Pendidikan, 2018)
The research examines on the improvement of Social Science Learning Result through the implementation of cooperative learning model of Explicit Instruction type to class IX.3 Students at SMP Negeri 2 Bontoramba in Jeneponto District. The objectives of the research are to discover : (1) The description of Social Science Learning Result of the students in class IX.3 at SMP Negeri 2 Bontoramba in Jeneponto District after implementin cooperative Learning model of Explicit Instruction type. (2) The description activiti students in class IX.3 at SMP Negeri 2 Bontoramba subdistrict of Jeneponto district in following learning Social Science by using of cooperative Learning Model of Explicit Instruction. (3) The description activities teacher in The Implementation of cooperative Learning Model of Explicit Instruction.            The research was classroom action research which conducted in two cycles. Each cycle consistedof four stages, namely : (1) planning,(2) action, (3) observation, and (4) reflection. The subjects of the research were one teacher and students in class IX.3 Students at SMP Negeri 2 Bontoramba Subdistrict of Jeneponto District with the total of 26 persons. The instruments of the research were observation sheets for the teachers and students, learning result test, and documentation. Data analysis  technique used is quantitatively descriptive with percentage.            The result of the first cycle test reveals that the average score achieves 69,69 which is in medium category. Out of 26 students,16 students (61,5%) had successfully reached the learning completeness and 10 students (38,5%) had not completed. The result of the secon cycle test indicates that the average score achieves 79,04 which is in very high category. Out of 26 students, 26 students (100%) had successfully achieved the learning completeness.            The results of the research showed that there was an increase in the results of learning Social Sciences  of Class IX.3 student at SMP Negeri 2 Bontoramba in Jeneponto District after implementedCooperative Learning Model of Explicit Instruction Type.Keywords :   learning outcomes, student activities, teacher activities.Cooperative Learning Model of Explicit Instruction Type.